Active Razor Shell CaO Catalyst Synthesis for Jatropha Methyl Ester Production via Optimized Two-Step Transesterification - Reddy, Anr; Saleh, A.A.; Islam, M.S.; Sinin, Hamdan (Hindawi Publishing Corporation, 2017)
Calcium based catalysts have been studied as promising heterogeneous catalysts for production of methyl esters via transesterification; however a few were explored on catalyst synthesis with high surface area, less particle size, and Ca leaching analysis. In this work, an active Razor shell CaO with crystalline size of 87.2 nm,